1999
DOI: 10.1023/a:1024789723779
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse and sexual revictimization in a female Navy recruit sample

Abstract: To examine effects of childhood abuse on adult rape, 1,887 female Navy recruits were surveyed. Overall 35% of recruits had been raped and 57% had experienced childhood physical abuse (CPA) and/or childhood sexual abuse (CSA). Controlling for CPA, rape was significantly (4.8 times) more likely among women who had experienced CSA than among women who had not. In contrast, CPA (controlling for CSA) was unrelated to likelihood of adult rape. Alcohol problems and number of sex partners were examined as mediators. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
130
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(152 citation statements)
references
References 29 publications
16
130
1
5
Order By: Relevance
“…For example, in a sample of Navy recruits, women who had been raped were more likely than those who had not to be victims of childhood sexual abuse, to have many sexual partners, and to have drinking problems (Merrill et al, 1999). Similarly, Koss and Dinero (1989) found that college women who had experienced sexual assault in adolescence or adulthood were more likely than other college women to have experienced childhood sexual abuse, to have a larger number of sexual partners, and to drink more heavily.…”
Section: Childhood Sexual Abusementioning
confidence: 99%
“…For example, in a sample of Navy recruits, women who had been raped were more likely than those who had not to be victims of childhood sexual abuse, to have many sexual partners, and to have drinking problems (Merrill et al, 1999). Similarly, Koss and Dinero (1989) found that college women who had experienced sexual assault in adolescence or adulthood were more likely than other college women to have experienced childhood sexual abuse, to have a larger number of sexual partners, and to drink more heavily.…”
Section: Childhood Sexual Abusementioning
confidence: 99%
“…Specifically, 45.5 percent (« = 834) of female Navy recruits had been the victim of an attempted rape; 9.4 percent, (n = 173) and 36.1 percent (« = 661) had been the victim of a completed rape since age 14. Similarly, additional research by this same group indicated that 26.0 percent and 35.0 percent of female Navy trainees had experienced rape and 7.6 percent and 8.0 percent reported attempted rape only (see Merrill et al, 1997Merrill et al, ,1999. A subsequent study by this same group of researchers found that 26 percent of female Navy recruits had experienced unwanted sexual contact before age 15 with someone at least five years older (Sinclair et al, 2001).…”
Section: Sexual Victimization Among Female Trainees Active-duty Andmentioning
confidence: 96%
“…Merrill and colleagues have conducted a series of studies that represent the most comprehensive research on premilitary experiences of sexual assault (see Merrill et al, 1996Merrill et al, ,1997Merrill et al, ,1999Merrill, Thomsen, Gold, & Milner, 2001;Sinclair, Merrill, Thomsen, & Gold, 2001). Specifically, 45.5 percent (« = 834) of female Navy recruits had been the victim of an attempted rape; 9.4 percent, (n = 173) and 36.1 percent (« = 661) had been the victim of a completed rape since age 14.…”
Section: Sexual Victimization Among Female Trainees Active-duty Andmentioning
confidence: 99%
See 2 more Smart Citations